CORRELATION ANALYSIS BETWEEN THE SERVICE QUALITY, CUSTOMER SATISFACTION, AND CUSTOMER LOYALTY OF VIVA GENERIK PHARMACY IN SEMARANG - Eva Monica; Basu Swastha Dharmmesta; Suci Paramitasari Syahlani (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2017)
Today, pharmacy service has become more developed along with the enhancement of society awareness of the importance of health. Therefore, as one of the health service facilities, pharmacy is required not only to give priority on product prices and varieties but also to provide qualified service for the patients. Viva Generik pharmacy as a new comer should have the ability to understand the situation and should have the competitive advantage. This study used a survey method. Data were collected with a purposive sampling method using the instrument of closed questionnaires. The questionnaires were tested for the validity and the reliability to 40 respondents who were the consumers of Viva Generik pharmacy. Questionnaires were given to 150 respondents, then were analyzed using qualitative descriptive statistics to identify the respondents characteristic. Quantitative analysis was used to identify the quality of the service and to see the correlation between service quality, satisfaction, and customer loyalty of Viva Generik pharmacy. As a result, Viva Generik pharmacys consumers tended to agree that the quality of service given by Viva Generik pharmacy was good. Simultaneously, service quality variables gave a positive impact to the customer satisfaction and the customer loyalty. It was just the tangible dimension that gave the significant impact on the customer satisfaction and customer loyalty. It was also disclosed that the customer satisfaction brought a significant impact on the customer loyalty to Viva Generik pharmacy.